Dark Matter: Could It Be Vacuum Viscosity? - M. B. Altaie; N. R. Suleiman; N. M. Ershaidat (Jordan Journal of Physics, 2025)
We test a hypothesis that stars located away from the center of the galaxy,moving under the effect of an emergent viscous drag force perpendicular to their velocities, might exhibit the behavior observed in the rotation curves of the spiral galaxies. We construct a simple model for such an assumption, then by using simple fitting technique, we are able to produce the rotation curves for a sample of 18 spiral galaxies. Results show good agreement with the observed rotation curves. The applicability of our hypothesis suggests that an emergent drag force perpendicular to the velocity of the stars might be the cause of the apparent dark matter effect. Keywords: Rotation curves, Quantum vacuum, Dark matter. PACS: 95.30.Sf, 95.35.+d